2008
DOI: 10.1016/j.drugalcdep.2007.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Brain macrostructural and microstructural abnormalities in cocaine dependence

Abstract: Rationale-Two previous studies have utilized Diffusion Tensor Imaging (DTI) to examine microstructural integrity in cocaine abuse and found evidence of brain abnormalities in white matter.Objective-Using anatomical magnetic resonance imaging (MRI), DTI, and clinical evaluation, the macrostructural and microstructural correlates of cocaine abuse were investigated.Methods-21 men and women (mean age 42.5, mean 18.9 years of cocaine use) and 21 age/gendermatched controls were included. Fractional anisotropy (FA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
115
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 39 publications
13
115
3
3
Order By: Relevance
“…This finding was replicated in a second study performed by the same group (Lim et al, 2008). Moeller et al (2005) performed DTI in 18 cocainedependent subjects and 18 healthy controls, focusing on the corpus callosum.…”
Section: Utilizing Diffusion Tensor Imaging As a Potential Toxicity Bsupporting
confidence: 64%
“…This finding was replicated in a second study performed by the same group (Lim et al, 2008). Moeller et al (2005) performed DTI in 18 cocainedependent subjects and 18 healthy controls, focusing on the corpus callosum.…”
Section: Utilizing Diffusion Tensor Imaging As a Potential Toxicity Bsupporting
confidence: 64%
“…In our study, negative correlations between impulsivity and the FA values of the right CST were found in the HCs, which was consistent with the results of Olson's studies. Kelvin's voxel-wise correlation analysis also indicated that low FA values of the posterior crus of the internal capsule are associated with increased impulsivity as measured by the BIS-11 in chronic cocaine users (Lim et al, 2008). These results suggest that the altered correlations between impulsivity and the FA values of the CST in the IGD adolescents might reflect potential WM microstructural changes that may be associated with the greater impulsivity of IGD adolescents.…”
Section: T a B L Ementioning
confidence: 56%
“…Some of these findings have also been reported by Joutsa et al (2011) such as a reduced FA in the anterior thalamic radiation, the inferior longitudinal fascicle, Yip et al (2013) also showed a reduced fractional anisotropy in the genu of the corpus callosum in PG. Joutsa et al (2011) point out that similar changes have also been seen in substance abuse disorders (e.g., Lim et al 2008;Xu et al 2010). Further, the superior longitudinal fascicle (Lim et al 2008;Ashtari et al 2009;Jacobus et al 2009;Pfefferbaum et al 2009;Yeh et al 2009;Lane et al 2010;Xu et al 2010), the inferior longitudinal fascicle (Jacobus et al 2009;Yeh et al 2009) and the inferior fronto-occipital fascicle (Yeh et al 2009) have been seen in previous DTI studies pointing to a general susceptibility to addictions for subjects presenting with a reduced FA in these tracts.…”
Section: Differences Between Pathological Gamblers and Healthy Controlsmentioning
confidence: 78%